Relación entre el manejo de los residuos sólidos domésticos de los padres con las actitudes hacia la conservación del medio ambiente en niños y niñas de cinco años de las instituciones educativas ubicadas en la zona urbano marginal del distrito de Rioja en el año 2010 - Chávez Rojas, Lucy (2011)
The research aimed to determine the relationship of the management of municipal solid waste of parents' attitudes towards environmental conservation in children five years of educational institutions located in the marginal urban area in the Rioja district 2010. Correlational research, the predictive level trans correlational design was developed with a sample of 19 parents and 19 children 5 years of age, which was applied to inventory management and domestic solid waste a survey of attitudes toward environmental conservation, respectively. The data obtained by administering these instruments were processed through the distribution of frequencies and Perason correlation coefficient, hypothesis testing was performed using the Student Act, was the correlation coefficient to be processed with the formula of T Student to see the significance of the correlation, to a level of 5% and the degrees of freedom n-2. Following the analysis of the results, it was concluded that the management of municipal solid waste of the parents was significantly related to attitudes toward environmental conservation in children five years of educational institutions located in marginal urban area Rioja district in 201 O. The ratio is the expression that scores on both variables are located at a low level, hence it is recommended that teachers and administrators of educational institutions located in marginal urban area in the district of Rioja, design, implement and run workshops aimed at training parents on management of domestic solid waste, as well as on the development of altitudes toward environmental conservation.